Temporal Trend in the Methods of Suicide in Kathmandu District: A Descriptive Study - Chaudhary, Gopal; Mandal, Bishal; Yadav, Bishal Kumar; Mahato, Abhishek; Basnet, Bishal; Sigdel, Bishal (Journal of Institute of Medicine Nepal, 2024)
Introduction Suicide is one of the major causes of death in Nepal. This study examines trends in suicide methods in Kathmandu, Nepal. The study aims to understand suicidal method changes over time and guide effective prevention strategies. Methods This study is descriptive study of autopsy data from the Department of Forensic Medicine at Maharajgunj Medical Campus, Kathmandu from January 2013 to December 2022. Linear regression analyzed changes in suicide rates by gender and method over time. Chi-square tests assessed monthly frequency deviations. Data was stratified by age groups and sex to identify any potential correlations between these variables and the methods of suicide used. Results Among 2,513 males suicide, the most common method was hanging accounting for 1,633 (64.98%) cases, followed by self-poisoning at 806(32.07%) cases, with falls and self-immolation each at 1.31%. For 1,905 females suicide, hanging remained the most prevalent method with 1,215 (63.77%) cases, followed by self-poisoning at 622 (32.65%) cases, with falls (0.57%) and self-immolation (2.78%) being less common. The mean age for male suicides was 37.15(SD=15.83), while for females it was 30.94 (SD=14.20), indicating a difference of 6.21 years. Suicide rates peaked in summer (July-August) with 450 cases and dropped in winter (December-February) at 309 cases. Conclusion Hanging was the most common method of suicide across all age groups, though its prevalence declined with age. In contrast, self-poisoning became more common as age increased. The study depicted that females tend to commit suicide at relatively younger age than males. Significant seasonal variations in suicide rates were observed.